Surface Charge Transfer Enhanced Cobalt‐Phthalocyanine Crystals for Efficient CO2‐to‐CO Electroreduction with Large Current Density Exceeding 1000 mA cm−2 - Tengyi Liu; Di Zhang; Yutaro Hirai; Koju Ito; Kosuke Ishibashi; Naoto Todoroki; Yasutaka Matsuo; Junya Yoshida; Shimpei Ono; Hao Li; Hiroshi Yabu (Advanced Science)
Abstract Phthalocyanines (Pcs) have garnered significant attention as promising catalysts for electrochemical CO2 reduction (ECR); however, traditional methods for preparing carbon‐supported Pcs are often complex and time‐consuming, limiting their industrial applicability. Herein, a rapid spray‐growth method is introduced that directly deposits CoPc crystals onto carbon paper (CP) in just 15 min. The resulting CoPc/CP electrode maintains > 90% CO selectivity across a broad ECR window (−0.57 to −1.32 V vs RHE), achieves a record‐breaking CO current density of −1034 mA cm−2, an ultrahigh mass activity of 5180 A g−1, and demonstrates excellent long‐term stability (145 h @ −150 mA cm−2), surpassing all reported Pc‐based catalysts. Comprehensive characterization attributes this high performance to its carbon‐supported‐crystalline structure and surface charge transfer (SCT). Density functional theory (DFT) calculations further reveal that even minimal SCT effectively optimizes the adsorption energies of key intermediates (*CO and *COOH), thereby significantly enhancing intrinsic activity. Moreover, this spray‐grown electrode offers unique structural advantages, such as strong substrate adhesion and internal layers that replenish active sites—features absent in traditional carbon‐supported electrodes. It is believed that this facile spray‐growth method holds broad potential and enables the application of additional Pc‐based materials for industrial‐scale ECR.